Dose assessment due to natural gamma radiation levels and radioactive nuclides in the environment of Dasarlapally, Nalgonda District, Telangana State, India. Issue 19 (30th December 2022) - Suman, G.; Vinay Kumar Reddy, K.; Sreenath Reddy, M.; Vidyasagar, D.; Gopal Reddy, Ch.; Yadagiri Reddy, P.
ABSTRACT: Gamma radiation levels in the indoors and outdoors of Dasarlapally, a village in the environs of uranium mineralised area, were measured with μR- survey metre and Thermoluminescence Dosimeters (TLDs). The measured gamma radiation absorbed dose in the study area varied between 1744 and 2663 µGy y −1 with an average of 2327 ± 505 µGy y −1 . The ratio of indoor to outdoor gamma radiation levels was found to be varied from 0.92 to 1.54 with an average of 1.09. The soil samples were analysed for radioactive elements 226 Ra, 232 Th and 40 K using gamma ray spectrometer and found that the concentration of radioactive nuclides, radium and thorium, is three times and five times higher than global average, respectively, whereas the potassium activity is lower than the global. The external absorbed dose rate due to radioactive nuclides present in the soil and associated hazard index parameters were also calculated.